2015
DOI: 10.3233/wor-141971
|View full text |Cite
|
Sign up to set email alerts
|

Experience of switching from a traditional sitting workstation to a sit-stand workstation in sedentary office workers

Abstract: Prolonged sedentary time (ST) is associated with adverse health outcomes, while decreasing ST improves health outcomes. The use of sit-stand desks (SSDs) in workplaces has been proposed as a means of reducing ST. The purpose of this study was to gain knowledge about participants' experience and perceptions of a workplace intervention involving the introduction of SSDs. Focus groups and interviews were conducted with 28 study participants who used SSDs for 4 weeks. Data were analyzed using a grounded theory app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…musculoskeletal problems) during the trial as whole [17], participants in these qualitative interviews perceived that the increased workplace standing time had had positive impacts on alertness, concentration and energy, and for some, had relieved their musculoskeletal complaints. These observations are consistent with a growing body of research suggesting that workers perceive a range of health and well-being benefits from using a sit-stand workstation [15, 16, 20]. However, despite the potential for sit-stand workstations to be an effective health promoting strategy, previous studies have suggested that the workstations are viewed as an aid for addressing pre-existing musculoskeletal conditions, rather than for preventive health [21, 22].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…musculoskeletal problems) during the trial as whole [17], participants in these qualitative interviews perceived that the increased workplace standing time had had positive impacts on alertness, concentration and energy, and for some, had relieved their musculoskeletal complaints. These observations are consistent with a growing body of research suggesting that workers perceive a range of health and well-being benefits from using a sit-stand workstation [15, 16, 20]. However, despite the potential for sit-stand workstations to be an effective health promoting strategy, previous studies have suggested that the workstations are viewed as an aid for addressing pre-existing musculoskeletal conditions, rather than for preventive health [21, 22].…”
Section: Discussionsupporting
confidence: 83%
“…However, evidence reviews have suggested that greater impacts on workplace sitting may be achieved if sit-stand workstations are implemented as part of a broader approach that addresses the multiple levels of influence on behaviour [5, 11, 12]. While previous qualitative studies have assessed workers’ perspectives of sit-stand workstations in isolation [1316], there is limited knowledge about the feasibility and acceptability of incorporating them within a multi-component, participatory workplace intervention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies on the placement of SSDs as an intervention to decrease sedentary behaviour have reported promising results (Alkhajah et al, 2012;Chu et al, 2016;Dutta, Walton, & Pereira, 2015). However, a closer look at SSD effectiveness studies reveals that placing SSDs led only to a reduction in sitting for a brief period (Dutta et al, 2015;Pronk et al, 2012). For example, an evaluation study in four different companies that placed SSDs found that 59.8% of the employees used their SSD at standing height only once a month or less.…”
mentioning
confidence: 99%